2002
DOI: 10.1111/j.1751-8369.2002.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Siberian river run-off and Late Quaternary glaciation in the southern Kara Sea, Arctic Ocean: preliminary results

Abstract: The extent of the Barents‐Kara Ice Sheet during the eastern Last Glacial Maximum (LGM) is not yet fully known. A detailed echo‐sounding survey performed during the Boris Petrov Expedition 2001 permitted the detailed mapping of part of it. Based on the profiling results, a southern connection between the LGM Barents‐Kara Ice Sheet and a local ice sheet on Taymyr Peninsula appears to be unlikely. Based on sediment core data and profiling results, most of the terrigenous river‐derived material accumulated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Svendsen et al ., ], has since indicated that the Kara Sea was largely ice free during the LGM. North of ~75°N and east of ~60°E toward Novaya Zemlya, seismic profiling and sediment cores have identified a strongly furrowed facies associated with morainic features, bounded to the southeast by paleo–river channels and basin‐fill deposits (Figure d) [ Polyak et al ., ; Stein et al ., ]. The inferred ice sheet limit aligns with a well‐defined moraine ridge southeast of the Novaya Zemlya Trough (Figure e) [ Svendsen et al ., ].…”
Section: Marginal Limitsmentioning
confidence: 99%
“…Svendsen et al ., ], has since indicated that the Kara Sea was largely ice free during the LGM. North of ~75°N and east of ~60°E toward Novaya Zemlya, seismic profiling and sediment cores have identified a strongly furrowed facies associated with morainic features, bounded to the southeast by paleo–river channels and basin‐fill deposits (Figure d) [ Polyak et al ., ; Stein et al ., ]. The inferred ice sheet limit aligns with a well‐defined moraine ridge southeast of the Novaya Zemlya Trough (Figure e) [ Svendsen et al ., ].…”
Section: Marginal Limitsmentioning
confidence: 99%
“…Some Russian authors assume that it extended over Spitsbergen, Franz Josef Land, Novaya Zemlya archipelagoes, and adjacent sea bottom, but not over the southern Barents Sea (e.g., Matishov 1984;Pavlidis 1992;Samoylovich et al 1993;Tarasov et al 1999Tarasov et al , 2000. Atlantic water likely penetrated to the Kara Sea as well, but the ice sheet extension was restricted here to western and possibly northern areas Mangerud et al 1999Mangerud et al , 2002Mangerud et al , 2004Polyak et al 2000aPolyak et al , 2002cStein et al 2002;Color Fig. According to many authors, the Barents-Kara ice sheet united with the Scandinavian ice sheet was up to 2-3-km thick (Lambeck 1995Landvik et al 1998;Elverhøi et al 1998).…”
Section: The End Of the Last Glaciationmentioning
confidence: 82%
“…The upper part of core PS2718/6 was lost during the coring, and the middle part is barren Plate 4.5 Reconstruction of the Eurasian ice sheet at the Last Glacial Maximum (LGM), about 20 ka BP (after Svendsen et al 2004 with additions). Boris Petrov is marked by solid red line (modified from Stein et al 2002). Red circles indicate location of reference cores used in Chapter 4 Plate 4.6 Maximum and minimum ice sheet boundary in the Kara Sea at the LGM according to different authors.…”
Section: Resultsmentioning
confidence: 99%
“…The initial evidence has demonstrated that in general the LGM glacigenic diamicton extends eastwards across the northern Kara Sea, sparing its more southern areas (Polyak, Gataullin et al. 2002; Stein et al. 2002).…”
Section: Glacial‐geological Context In the Barents And Kara Seasmentioning
confidence: 99%